The Effect of the Relationship of Growth Return and Market Value on the Relationship of Liquidity and Company Value Growth - OGAILI, Sabah Hasan (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The purpose of the research was to demonstrate the relationship between growth the return and the market value as two intermediate variables by comparing its relationship with liquidity and growth the value of the company. A set of financial ratios for the sample banks was used for the quantitative analysis using SPSS statistical analysis software to validate these hypotheses. The study included an elected sample gathered from some Iraqi private banks for the period (2013 – 2017), and demonstrated strong correlations between liquidity as an independent variable versus growth the return and the market stock price. This is achieved by understanding the effects of growth the value of the company and the impact relationship of growth the return and the market stock prick as two intermediate variables in the relationship between liquidity and growth the value of the company.  Unlike previous publish articles which were limited to studying and testing the effect and relationship of one or two variables, this research explains the relationship between two intermediate variables influencing the relationship of other two variables.